Platelets, glycoprotein Ib-IX, and von Willebrand factor are required for FeCl3-induced occlusive thrombus formation in the inferior vena cava of mice. (May 2013) - Joglekar, M.V.; Ware, Jerry; Xu, Jin; Fitzgerald, Malinda E. C.; Gartner, Theodore Kent
<x xml:space="preserve">Abstract</x> Venous thromboembolism is a leading cause of death from cardiovascular disease. Despite the importance of the glycoprotein (GP) Ib-IX/von Willebrand factor (vWF) axis in arterial thrombosis, its requirement in venous, not venule thrombosis in response to endothelial injury (not stenosis or stasis) is uncharacterized. GPIbα-vWF participation in FeCl3-induced thrombus formation was evaluated in the inferior vena cava (IVC). Stable, occlusive thrombus formation in response to FeCl3-induced injury of the IVC was studied. FeCl3 (20% FeCl3, 10 minutes)-induced occlusive thrombosis required platelets as confirmed by a lack of occlusion in thrombocytopenic mice, and stable occlusion in control animals. No IVC occlusion was observed using GPIbα-deficient animals, a model of the human Bernard-Soulier syndrome (BSS). Transgenic IL-4 R/GPIbα mice (lack murine GPIbα, but express the extracellular domain of the human interleukin (IL-4 receptor fused to the transmembrane and cytoplasmic domains of human GPIbα) were studied to determine if the absence of IVC occlusion in the BSS mouse was caused by GPIbα extracellular domain deficiency rather than platelet BSS phenotype associated abnormalities. As with GPIbα knock-out mice, no occlusion was observed in the IVC of IL-4 R/GPIbα mice. The IVC of vWF-deficient mice also failed to occlude in response to FeCl3 treatment. The chimeric protein GPIbα(2V)-Fc prevented occlusion, demonstrating that GPIbα-vWF A1 domain interaction is required for FeCl3-induced stable thrombus formation in the IVC. Therefore, FeCl3-induced stable, occlusive thrombus formation in the IVC is platelet, and apparently GPIbα-vWF interaction dependent, despite the large diameter and low venous flow rate in the IVC.